Banking Competition and Economic Growth: 2006-2015 Case of Rwanda - Faustin Maniraguha (RIRAI Publisher, 2020)
It has been argued that a competitive and efficient financial sector is a prerequisite for economic growth and development. The objective of this study therefore was to determine the influence of bank competition on economic growth in Rwanda for the period 2006 - 2015.The study used Error Correction Model after conducting Unit Root Test(ADF) and Cointegration Test(Johansen) so that to check the degree of adjustment in the short run. The results revealed that Credit to GDP is highly significant and this implied that there is a need to set the policy influencing credit distribution in order to influence economic growth. In addition disequilibrium found in the short run is corrected quarterly at 70.32%.